Visual stimuli recognition asymmetry in probabilistic prognosing - Kočiūnas , R. (Psichologija, 1981)
The aim of this investigation was to determine the dependence of the recognition asymmetry of different curvature bows on the probability of stimuli appearance in one of visual half-fields. Under monocular condition the quality of correct recognitions as well as the character of asymmetry largely depends on the probability of stimuli presentation. Under dichoptic condition the asymmetry depends on the probability of the appearance of monocular stimuli scattered among dichoptic pairs in one of visual half-fields.